Analysis of Granting Polygamy Permits in Marriage Based on Islamic Law and Law Number 16 of 2019 - Aulya, Fahrysyah; Manurung, Depi Yohana; Tampubolon, Sarah Lestari; Pasaribu, Dyna MT; Halimah, Halimah; Siahaan, Parlaungan Gabriel; Hadiningrum, Sri (CV. Rayyan Dwi Bharata, 2024)
This research discusses the analysis of granting permission for polygamy in marriage based on Islamic law and Law Number 16 of 2019 in Indonesia. In Islamic law, polygamy is permitted with a maximum limit of four wives and the main condition is to treat the wives fairly. Meanwhile, the Marriage Law in Indonesia regulates polygamy more strictly by requiring permission from the Religious Court. To obtain permission for polygamy, a husband must fulfill conditions such as the wife's consent, certainty of being able to meet the needs of his wife and children, and a guarantee that he will be treated fairly. Even though it is strictly regulated, there are still pros and cons regarding the permissibility of polygamy, both from a religious and human rights perspective. Some parties consider it discrimination against women and children, while other parties see it as part of religious teachings that must be respected. This research emphasizes the importance of balance in the application of religious law and state law regarding polygamy, as well as protecting the rights of wives and children.